THE FUNDAMENTAL PRINCIPLES OF THE CONSTITUTION OF THE REPUBLIC OF POLAND (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
One of the most important tasks of contemporary democratic states, beingsimultaneously a real challenge for them, is guaranteeing a stable processof their dynamic and effective development, based on the democraticprinciples expressed in their constitutions jointly with their practical andeffective implementation. Among others, one of the main states’ tasks isalso guaranteeing fundamental rights and freedoms to its citizens andpeople, as well as enabling them their proper exercising and strictobservance. The hereby paper aims at conducting a detailed legal analysisof the catalogue of fundamental principles contained in the Constitutionof the Republic of Poland of 1997, being presently in force, along withreflecting over their content and scope, as well as discussing their sourcesand axiological basis deriving from the output of Polish constitutionallaw doctrine, the doctrine of other developed democratic states andinternational standards.